KOMUNIKASI PARIWISATA BUDAYA MELAYU DINAS PARIWISATA KABUPATEN SIAK DALAM MEMBENTUK BRAND DESTINATION SIAK THE TRULY MALAY - Dinanty, Aditta Riska; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Siak Regency is one of the districts with its capital, Siak Sri Indrapura, in Riau Province. Siak Regency is a developing area and is known for its strong Malay culture, Siak has great potential in improving the tourism sector in its area. This is one of the great assets for the siak government to develop existing tourism in Siak namely through the Siak Brand The Truly Malay which has been echoed by the Siak Regency Tourism Service and even the Truly Malay Tagline has officially become the copyright of Siak Regency. The tagline has been the 'soul' in the development of culture and tourism in the country of the Palace. Therefore the purpose of this research is to find out the process of communication of Malay Culture Tourism of Siak Regency Tourism Office in Forming the Trak Malay Siak Destination Brand.This study used qualitative research methods. Data collection techniques used in this study were interviews, observation, and documentation. The research subjects were 8 people, using a purposive technique chosen from the Siak Regency Tourism Office amounting to 3 people and using accidental techniques from the community or visitors totaling 5 people. Data collection is done through interviews, observation and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations using the technique of checking the validity of the data, namely the extension of participation and triangulation.The results of this study indicate that the Source or source in forming the Truly Malay Siak Destination Brand is the Tourism Office who has the ability to communicate and knowledge in forming the Truly Malay Siak Destination Brand is certainly owned by people who really work to carry out tourism development Siak, supported by the local government of Siak Regency and the siak community itself. The message or message used is persuasive and informative which is very interesting. Use of channels or media through, online media, social media and print media such as banner newspapers and billboards. Receivers in this case are domestic and foreign tourists.